2008
DOI: 10.1620/tjem.214.341
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Impairs Spatial Memory in Rats at a Specific Dose Level

Abstract: Statins, inhibitors of cholesterol synthesis, are used to prevent cardiovascular complications. Moreover, statins have been shown to influence some cognitive functions. The modulating effects of simvastatin, one member of the statin family, on memory-related neurotransmitters and neuronal structures have also been reported. We aimed to investigate the behavioral effects of long-term simvastatin application on daily activity, psychomotor performance and spatial memory using Sprague-Dawley rats. Simvastatin (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Statins are strong HMGR inhibitors widely prescribed in therapies against hypercholesterolemia and their benefits in preventing atherosclerosis and other cardiovascular diseases are incontrovertible. Recently, it has been reported that high-dose statin treatment induces effects in emotional, learning, and memory processes (Kilic et al, 2012;Douma et al, 2011;Baytan et al, 2008;While and Keen, 2010). However, the role of the MVA biosynthetic pathway in the modulation of emotional behavior and cognitive performance is still unclear because of the lack of systematic studies on the causal link between the activation of this metabolic pathway and behavioral and cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Statins are strong HMGR inhibitors widely prescribed in therapies against hypercholesterolemia and their benefits in preventing atherosclerosis and other cardiovascular diseases are incontrovertible. Recently, it has been reported that high-dose statin treatment induces effects in emotional, learning, and memory processes (Kilic et al, 2012;Douma et al, 2011;Baytan et al, 2008;While and Keen, 2010). However, the role of the MVA biosynthetic pathway in the modulation of emotional behavior and cognitive performance is still unclear because of the lack of systematic studies on the causal link between the activation of this metabolic pathway and behavioral and cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Control animals received equivalent volumes of saline by the same route. In the rat statins are generally given by oral gavage, to mimic the situation in the clinic whereby the inactive simvastatin lactone is hydrolyzed in the liver to the open acid active form of the drug (Gazzerro et al, 2012), at doses between 10 and 60 mg/kg/day (e.g., Delbosc et al, 2002; Baytan et al, 2008; Renno et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Drugs were administered between 4 and 5pm daily, at least 2 hrs after testing and 16hrs before the next behavioural experiment. The choice of dose was based on previous behavioural studies using statin treatments ( [28] 1, 5mg/kg [21]; 10 and 30 mg/kg [29]; 10mg/kg). Clinical trial doses of pravastatin and atorvostatin are in the region of 40mg and 10mg respectively, in line with the higher relative potency of atorvastatin [30].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, simvastatin enhances long-term potentiation (LTP) in hippocampal slices in vitro and stimulates hippocampal neurogenesis and expression levels of neurotrophic factors such as brain derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) [1820]. With the exception of a recent study by Baytan et al (2008) [21], demonstrating a statin-induced impairment of spatial memory in naïve rats, data regarding the effects of statin treatment in vivo without prior manipulation of cognitive function is lacking. Since cholesterol is essential in the myelination of neurons and other neuronal functions, it has been proposed that excessive inhibition of cholesterol synthesis could lead to adverse cognitive effects [22].…”
Section: Introductionmentioning
confidence: 99%